x 3 − 2 x 2 − 5 x + 6 x 2 − 1 9 = x − 1 A + x + 2 B + x − 3 C
Let A , B and C be constants satisfying the partial fraction decomposition above. Find A × B × C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Partial Fractions
x 3 − 2 x 2 − 5 x + 6 x 2 − 1 9 = x − 1 A + x + 2 B + x − 3 C
( x − 1 ) ( x + 2 ) ( x − 3 ) x 2 − 1 9 = ( x − 1 ) ( x + 2 ) ( x − 3 ) A ( x + 2 ) ( x − 3 ) + B ( x − 1 ) ( x − 3 ) + C ( x − 1 ) ( x + 2 )
( x − 1 ) ( x + 2 ) ( x − 3 ) x 2 − 1 9 = ( x − 1 ) ( x + 2 ) ( x − 3 ) A ( x 2 − x − 6 ) + B ( x 2 − 4 x + 3 ) + C ( x 2 + x − 2 )
( x − 1 ) ( x + 2 ) ( x − 3 ) x 2 − 1 9 = ( x − 1 ) ( x + 2 ) ( x − 3 ) ( A + B + C ) x 2 + ( C − A − 4 B ) x + ( 3 B − 6 A − 2 C )
Then we can set equations for the coefficients of the numerator:
⎩ ⎪ ⎨ ⎪ ⎧ A + B + C = 1 C − A − 4 B = 0 3 B − 6 A − 2 C = − 1 9
Adding the first two equations, we will get 2 C − 3 B = 1 , and by adding this to the last equation, we will come up with: − 6 A − 1 = − 1 9 . Thus, A = 3 .
Then, C = − B − 2 .
− B − 2 − 3 − 4 B = − 5 B − 5 = 0 . Thus, B = − 1 .
Hence, C = − 1 .
Therefore, A × B × C = 3 × − 1 × − 1 = 3 .
For partial fractions with linear denominators, I generally prefer to use the cover up rule as it's much more immediate (and less error prone).
Did the same..
Nice approach, another way to solve partial fraction expansion using linear equations in three variable s.
x 3 − 2 x 2 − 5 x + 6 x 2 − 1 9 ( x − 1 ) ( x + 2 ) ( x − 3 ) x 2 − 1 9 x 2 − 1 9 Let x = 1 : 1 − 1 9 ⟹ A Let x = − 2 : 4 − 1 9 ⟹ B Let x = 3 : 9 − 1 9 ⟹ C = x − 1 A + x + 2 B + x − 3 C = x − 1 A + x + 2 B + x − 3 C Multiply both sides by ( x − 1 ) ( x + 2 ) ( x − 3 ) = A ( x + 2 ) ( x − 3 ) + B ( x − 1 ) ( x − 3 ) + C ( x − 1 ) ( x + 2 ) = A ( 3 ) ( − 2 ) + B ( 0 ) + C ( 0 ) = 3 = B ( − 3 ) ( − 5 ) = − 1 = C ( 2 ) ( 5 ) = − 1
⟹ A × B × C = ( 3 ) ( − 1 ) ( − 1 ) = 3
Using cover up method from wiki we get the following.
A
=
(
x
+
2
)
(
x
−
3
)
x
2
−
1
9
∣
x
=
1
=
(
1
+
2
)
(
1
−
3
)
1
2
−
1
9
=
3
.
B
=
(
x
−
1
)
(
x
−
3
)
x
2
−
1
9
∣
x
=
−
2
=
(
−
2
−
1
)
(
−
2
−
3
)
(
−
2
)
2
−
1
9
=
−
1
.
C
=
(
x
−
1
)
(
x
+
2
)
x
2
−
1
9
∣
x
=
3
=
(
3
−
1
)
(
3
+
2
)
3
2
−
1
9
=
−
1
.
∴
A
∗
B
∗
C
=
3
Problem Loading...
Note Loading...
Set Loading...
x 3 − 2 x 2 − 5 x + 6 x 2 − 1 9 = x − 1 A + x + 2 B + x − 3 C
⇒ x 2 − 1 9 = A ( x + 2 ) ( x − 3 ) + B ( x − 1 ) ( x − 3 ) + C ( x − 1 ) ( x + 2 )
⎩ ⎪ ⎨ ⎪ ⎧ x = 1 ⇒ 1 8 = − 6 A ⇒ A = 3 x = − 2 ⇒ − 1 5 = 1 5 B ⇒ B = − 1 x = 3 ⇒ − 1 0 = 1 0 C ⇒ C = − 1
⇒ A B C = − 1 × 3 × − 1 = 3